2002
DOI: 10.1149/1.1423642
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Enhanced Atomic Layer Deposition of Ta-N Thin Films

Abstract: The plasma-enhanced atomic layer deposition ͑PEALD͒ of tantalum nitrides ͑TaN͒ thin films has been performed using terbutylimidotris͑diethylamido͒tantalum and hydrogen radicals at a temperature of 260°C. The film thickness per cycle is also self-limited at 0.8 Å/cycle, which is thinner than that of the conventional atomic layer deposition ͑ALD͒, 1.1 Å/cycle. X-ray diffraction analysis indicates that the as-deposited films are not amorphous but polycrystalline mixed with cubic TaN and TaC. The film crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 12 publications
7
98
1
Order By: Relevance
“…Using 30 s H 2 plasma in the ALD cycle resulted in a resistivity as low as 380 ⍀ cm which is similar to the best values reported in the literature ͑350-400 ⍀ cm͒. 4,9 Park et al reported that the decrease in resistivity relates to an increase in mass density and degree of crystallization of the TaN x films. 9 We note that one data point ͑3 s H 2 plasma͒ does not follow the general trend and the corresponding film was specifically investigated for its low resistivity ͑FPP: 48 ⍀ cm͒.…”
Section: -7supporting
confidence: 82%
See 4 more Smart Citations
“…Using 30 s H 2 plasma in the ALD cycle resulted in a resistivity as low as 380 ⍀ cm which is similar to the best values reported in the literature ͑350-400 ⍀ cm͒. 4,9 Park et al reported that the decrease in resistivity relates to an increase in mass density and degree of crystallization of the TaN x films. 9 We note that one data point ͑3 s H 2 plasma͒ does not follow the general trend and the corresponding film was specifically investigated for its low resistivity ͑FPP: 48 ⍀ cm͒.…”
Section: -7supporting
confidence: 82%
“…% reported by Kim et al 4 and the C content of 20 at. % reported by Park et al 9 The C content in the films originates from the PDMAT ligands and could not effectively be reduced by prolonged plasma exposure time as indicated by our experiments. Showing a different trend than the N and O content with H 2 plasma exposure time, the constant C content could be an indication of a redeposition process involving ligand surface reaction products dissociated by the plasma after being released from the surface.…”
Section: -7contrasting
confidence: 44%
See 3 more Smart Citations